Analysis Problem of Air Bleed Maintenance Message Using Fault Tree Analysis (FTA) Method - Kater, Jimi; Adiputra, Bangga Dirgantara; Mulyani, Sri; Priyahapsara, Istyawan; Rahmawati, Fajar Khanif; Prattiwi, Elisabeth Anna (Institut Teknologi Dirgantara Adisutjipto, 2025)
The Airbus A320 has two main engines and an Auxiliary Power Unit (APU) that generate high-temperature, high-pressure bleed air used for cabin cooling, anti-icing, and pressurization. Two temperature sensors, Fire Loop A and Fire Loop B, monitor the bleed air distribution line for hot air leaks. An Air Bleed Maintenance Message signals a malfunction in these fire protection loops and requires quick maintenance to avoid system failure. Leaks, especially near the wing and fuel tank, pose significant hazards. This study uses Fault Tree Analysis (FTA) to find the root causes of this message. The main causes identified are damaged interconnecting cables, failure in the Bleed Monitoring Computer (BMC), and faults in Fire Loop A or B. The FTA diagram helps technicians trace each component's role in the failure, aiding efficient inspection and maintenance. This method aims to boost system reliability and improve flight safety.